A New Chromogenic Reagent for Determination of Copper (II) in Water Samples Using Flow injection-Technique. - Al-Abachi, Mouayed Q.; Abed, Sadeem Subhi; Al-Najjar, Nada Ali (Iraqi Journal of Science, 2022)
A new flow injection spectrophotometric method is described for the determination of copper ion Cu(II) in water samples (tap water and river water).The proposed method based on the formation of red complex [Cu(L)2(NO3)2] which has a maximum absorption at λmax=490 nm. Linear range for Cu (II) was from 5-70μg/mL with detection limit 2.55μg/mL. The effect of physical and chemical parameters were evaluated .The proposed method was applied successfully for determination of copper (II) in the tap and river water. [Cu(L)2(NO3)2] complex was prepared in a (2:1) mole ratio as ( reagent: copper (II)).The analytical reagent formed by reaction of thymol with 4-aminoantipyrine at room temperature. The metal complex was characterized by IR, UV-Visible spectra. The metal percentage, electrical conductivity and magnetic properties of the formed complex confirmed that this chromogenic reagent was coordinated with copper (II) metal ion through oxygen and nitrogen atoms of the phenol and amine group as a bidentate ligand with octahedral geometry.